Mathematical modeling of the source and environment response for the equation of geoelectrics - Iskakov, K.T.; Mukanova, B.G.; Berdyshev, A.S.; Kembay, A.S.; Tokseit, D.K. (Bulletin of the Karaganda University. Mathematics Series, 2019)
In this paper an algorithm is proposed for determining the source of excitation of electromagnetic waves emitted by the Ground - penetrating radar (GPR) device as a function of time. A mathematical model for solving this problem was constructed and tested on model data. We have built an algorithm for constructing a source function based on real georadar data. For this purpose, the results of experimental studies conducted in field conditions using the Loza-V GPR. Experiments were carried out in the medium: air - sand. The received signal of the response of the medium was processed from interference and noise. For this purpose, we use frequency filtering, signal averaging, amplitude correction for processing radarograms. In the future, the obtained table form of the disturbance signal will be used by us to study inhomogeneous media, including the study of localized objects. The series of calculations for the considered problems are given.